Produção de mudas de maracujazeiro-amarelo com diferentes tipos de enxertia e uso da câmara úmida - Silva, Roseano Medeiros da (2012)
The objective of this study was to evaluate the combination of three forms of grafting methods and use of protective grafting with moist chamber in the production of yellow passion fruit seedlings. The experimental design was a randomized complete block in a 3x2 factorial arrangement with six replications, each plot consisting of nine plants, where the factors were the combinations of three embodiments of the method of grafting (cleft, side slit and simple slot) with the use of grafting protection with moist chamber or not using it. Seeds from FB 100 passion fruit cultivar were used for production of rootstock plants. On the other hand, seeds from the rounded-yellow cultivar (Topseed® Company) were used for production of scions. Grafting were performed 70 days after sowing. After 21 days, grafts were removed from the protection of the moisture chamber. At this time, the effectiveness of grafts was evaluated. At 28, 42 and 56 days after grafting it was evaluated the amount of plants remained alive. Fifty six days after grafting it was evaluated the number of leaves, graft and rootstock diameter, plant height and shoot dry weight. There was a significant interaction for different types of grafting and use of moist chamber at 21 days after grafting. Types of grafting with the highest percentage of graft effectiveness were: cleft (94.45%) and side slit (91.67%). There was no influence on the use of protection with moist chamber for cleft and side slit. Cleft type grafting showed a decrease in the rate of fixation when not using moist chamber protection. Cleft grafting and side slit showed the higher rates of survival with 86.12% and 91.67% respectively for the 28, 42 and 56 days after grafting. Plants from grafts protected with moist chamber had the highest average survival percentage (79.63%) for 28, 42 and 56 days after grafting. The use of moist chamber caused a decrease in plant growth showing that there is a need for plants to remain in it much less than the used in the trial. Cleft and side slit grafting types associated with the use of protection promoted by moist chamber lowest rates of fixation and survival of seedlings of yellow passion